An Instructional Design For The Teaching Of English At SMP Muhammadiyah I Kartasura In 2013/2014 Academic Year A Naturalistic Study - Rifai, Dian Muhammad; , Prof. Dr. Endang Fauziati, M. Hum; , Dr. Dwi Haryanti, M.Hum (2014)
The study is aimed at analyzing the instructional design for the teaching of English at SMP Muhammadiyah I Kartasura in 2013/1014 academic year. In this research, there are nine component of instructional design, namely: (1) learning objective. (2) syllabus. (3)roles of instructional material. (4) classroom procedure. (5) classroom technique (6) teacher's role. (7) learner's role. (8) media. (9) evaluation model. The type of the study is descriptive qualitative especially naturalistic approach. In this research, the data are devired from event, informant, and field note. There are three techniques of collecting data, namely: observation, interview, and document. The techniques of analyzing data are data reduction, data display, and verification conclusion. The result of the study, such as: (1) There are two learning objective of teaching English especially in English teaching namely: general objective and specific objective. In general learning objective based on KTSP curriculum. In specific learning objective of teaching English is written in syllabus and it supported indicator of lesson plan. (2) The type of syllabus is notion functional syllabus.(3) the roles of instructional materials are as a resource for presentation materials, a source of actively for learner practice and communicative interaction, a reference source for learners on grammar, vocabulary, pronunciation and a source of stimulation and ideas for classroom activities, as a support for less experienced teachers (4) the classroom procedure used are Engagement, Exploration, Explanation, Elaboration and Evaluation and Genre Based Approach .(5) teaching technique used in teaching English are differentiate each skill 6) The teacher's role are facilitator, organizer, manager, assessor, planner and motivator.(7) the learner's role are learners plan their own learning program and this ultimately assumes responsibility for what they do in the classroom, group and learn by interacting with others, learner tutor other learners, 8) The media used in teaching learning process is used textbook and picture as printed media, video and images showed by using LCD.(9) Evaluation model used are daily examination, middle text and final test